p53 Acts as a Co-Repressor to Regulate Keratin 14 Expression during Epidermal Cell Differentiation - Cai, Bi-He; Hsu, Pei-Ching; Hsin, I-Lun; Chao, Chung-Faye; Lu, Mei-Hua; Lin, Hwang-Chi; Chiou, Shih-Hwa; Tao, Pao-Luh; Chen, Jang-Yi (PloS one, 2012)
During epidermal cell differentiation, keratin 14 (K14) expression is down-regulated, p53 expression varies, and the expression of the p53 target genes, p21 and 14-3-3σ, increases. These trends suggest that the relative transcriptional activity of p53 is increased during epidermal cell differentiation. To determine the relationship between K14 and p53, we constructed K14 promoters of various sizes and found that wild-type p53 could repress the promoter activity of all of the K14 promoter constructs in H1299 cells. K14-p160 contains an SP1 binding site mutation that prevents p53 from repressing K14 expression. Using a DNA affinity precipitation assay, we confirmed that p53 forms a complex with SP1 at the SP1 binding site between nucleotides -48 and -43 on the K14 promoter. Thus, our data indicate that p53 acts as a co-repressor to down-regulate K14 expression by binding to SP1. Next, we used a 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced epidermal cell differentiation model to examine the inhibition of K14 expression caused by increased p53 activity. Human ovarian teratocarcinoma C9 cells were treated with TPA to induce differentiation. Over-expression of the dominant negative p53 mutant ΔTAp53, which inhibits p53 activity, prevented the TPA-induced K14 down-regulation in C9 cells. Furthermore, treatment of normal primary human foreskin keratinocytes (PHFK) with the p53 inhibitor pifithrin-α (PFT-α) showed that the inhibition of p53 activity relieves K14 repression during epidermal cell differentiation. Finally, we found that TPA induces the phosphorylation of p53 at residue 378, which enhances the affinity of p53 to bind to Sp1 and repress K14 expression.